Penerapan Permainan Tradisional terhadap Peningkatan Lokomotor dan Non-Lokomotor pada Murid Sekolah Dasar - Listyana, Erni Eka Poetri; Tuasikal, Abdul Rachman Syam; Indahwati, Nanik (MAN Insan Cendekia Jambi, 2025)
The purpose of this study was to evaluate how traditional games impact the improvement of locomotor and non-locomotor skills in elementary school students. A quasi-experimental design was used. Thirty-eight fourth-grade students were divided into two groups: the experimental group (n=20) received traditional game-based learning, and the control group (n=18) received conventional physical education learning. The measurement instrument, developed based on the TGMD-2 indicators, was tested for reliability and validity. The experimental group showed significant improvements in locomotor skills (p = 0.000) and non-locomotor skills (p = 0.000), while the control group only showed significant improvements in locomotor skills (p = 0.022). On post-test scores for locomotor skills (p = 0.003) and non-locomotor skills (p = 0.000), an independent t-test revealed significant differences between the experimental and control groups. This study found that traditional game-based learning is more effective than conventional approaches in improving students' basic motor skills in elementary school. Therefore, it is recommended to incorporate traditional games into physical education (PJOK) learning as it is a contextual and enjoyable approach to teaching.